Enhanced Regeneration Through ex vitro Rooting and Agrobacterium-mediated Genetic Transformation of Eggplant (Solanum melongena L.) (Plant Tissue Culture and Biotechnology, 2021)
Regeneration of in vitro multiple shoots was achieved through organogenesis on MS supplemented with 2.0 mg/l BAP and 0.5 mg/l Kn from cotyledonary leaf explants of two local varieties of eggplant (Solanum melongena L.). Elongation of regenerated shoots was obtained on growth regulator free MS. In vitro root induction from excised regenerated shoots was less effective on MS with or without plant growth regulators. On the other hand regenerated shoots treated with 10 mM IBA for 5 min were found to be effective for ex vitro rooting in sterilized soil. Following sufficient development of roots, the ex vitro rooted plantlets were acclimatized in growth room condition, and were transferred to the field having 100% survival rate. The regeneration system developed was utilized for Agrobacterium-mediated genetic transformation using Agrobacterium tumefaciens strain LBA4404/pBI121 containing GUS and nptII genes. Adequate transformation response was obtained from cotyledonary leaf segments with bacterial suspension having an optical density of 0.50 at 600 nm with 30 min incubation followed by co-cultivation period of 72 hrs in Nayantara (BARI Begun-5) variety of eggplant. Selection of transformed shoots was carried out on MS supplemented with 2.0 mg/l BAP, 0.5 mg/l Kn, 300 mg/l carbenicillin and 100 mg/l kanamycin. Stable integration of GUS and nptII genes in Nayantara were confirmed through PCR analysis using the genomic DNA isolated from transformed shoots.Plant Tissue Cult. & Biotech. 31(1): 97-108, 2021 (June)